2021
DOI: 10.35940/ijrte.f5545.039621
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimization of Malware Detection using Extra-Tree and Random Forest Feature Selections on Ensemble Classifiers

Abstract: The proliferation of Malware on computer communication systems posed great security challenges to confidential data stored and other valuable substances across the globe. There have been several attempts in curbing the menace using a signature-based approach and in recent times, machine learning techniques have been extensively explored. This paper proposes a framework combining the exploit of both feature selections based on extra tree and random forest and eight ensemble techniques on five base learners- KNN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…(Cenggoro et al, 2019). The result showed that random forests (RF) have the highest performance in techniques for selecting features from RFs and extra trees for malware detection in ensemble classification (Gbenga et al, 2021). Additionally, it used RF, Boruta, and Recursive Feature Elimination (RFE) selection methods to select essential features and compare different machine learning for classification analysis.…”
Section: Introductionmentioning
confidence: 99%
“…(Cenggoro et al, 2019). The result showed that random forests (RF) have the highest performance in techniques for selecting features from RFs and extra trees for malware detection in ensemble classification (Gbenga et al, 2021). Additionally, it used RF, Boruta, and Recursive Feature Elimination (RFE) selection methods to select essential features and compare different machine learning for classification analysis.…”
Section: Introductionmentioning
confidence: 99%